An exploratory study on motivations, considerations, and intentions of child-free couples towards childbearing - Ang, Franchesca Marie B.; Lisama, Fionna Raine P.
This study employed a convergent mixed methods to explore the connection between childbearing motivations and childbearing considerations, and how they subsequently dictate their childbearing intention. To determine the childbearing motivations, a total of 80 child-free Filipino individuals from NCR accomplished an adaptation of Miller’s (1995) Childbearing Questionnaire (CBQ). Most of the participants were in the early adulthood stage, employed full-time, and working as professionals. Results from the CBQ revealed that 66.25% of the respondents had higher Negative Childbearing Motivation (NCM) scores than Positive Childbearing Motivation (PCM) scores, suggesting that their decision to remain child-free is strongly influenced by negative motivations and concerns related to childbearing. On the other hand, 10 participants were invited for a semi-structured interview to describe the considerations they take into account. Using thematic analysis, findings revealed that political, economic, sociocultural, relational, and personal reasons and concerns—especially those relating to pregnancy—play a significant role in shaping the childbearing decisions of couples. Furthermore, CBQ findings together with the interview responses were analyzed to support the identified childbearing intentions of the couple, reflecting the interplay between motivations and considerations, and how they shape intentions. This study presents several recommendations, including: expanding existing research instruments, exploring data through various demographic lenses, and maximizing the findings to develop more inclusive policies and programs for Filipino child-free couples.